Effect of a Family-Centered, Secondhand Smoke Intervention to Reduce Respiratory Illness in Indigenous Infants in Australia and New Zealand: A Randomized Controlled Trial. Issue 1 (25th August 2014) - Walker, Natalie; Johnston, Vanessa; Glover, Marewa; Bullen, Christopher; Trenholme, Adrian; Chang, Anne; Morris, Peter; Segan, Catherine; Brown, Ngiare; Fenton, Debra; Hawthorne, Eyvette; Borland, Ron; et al.
Abstract : Introduction: Secondhand smoke (SHS) is a significant cause of acute respiratory illness (ARI) and 5 times more common in indigenous children. A single-blind randomized trial was undertaken to determine the efficacy of a family centered SHS intervention to reduce ARI in indigenous infants in Australia and New Zealand. Methods: Indigenous mothers/infants from homes with ≥1 smoker were randomized to a SHS intervention involving 3 home visits in the first 3 months of the infants' lives (plus usual care) or usual care. The primary outcome was number of ARI-related visits to a health provider in the first year of life. Secondary outcomes, assessed at 4 and 12 months of age, included ARI hospitalization rates and mothers' report of infants' SHS exposure (validated by urinary cotinine/creatinine ratios [CCRs]), smoking restrictions, and smoking cessation. Results: Two hundred and ninety-three mother/infant dyads were randomized and followed up. Three quarters of mothers smoked during pregnancy and two thirds were smoking at baseline (as were their partners), with no change for more than 12 months. Reported infant exposure to SHS was low (≥95% had smoke-free homes/cars). Infant CCRs were higher if one or both parents were smokers and if mothers breast fed their infants. There was no effect of the intervention on ARI events [471 intervention vs. 438 usual care (reference); incidence rate ratio = 1.10, 95% confidence intervals (CI) = 0.88–1.37, p = .40]. Conclusions: Despite reporting smoke-free homes/cars, mothers and their partners continue to smoke in the first year of infants' lives, exposing them to SHS. Emphasis needs to be placed on supporting parents to stop smoking preconception, during pregnancy, and postnatal.